Clima laboral en la unidad administrativa - financiera de la coordinación del Ministerio de Inclusión Económica y Social (MIES) de la ciudad de Babahoyo - Campuzano Triguero, Anicia Shirlendy (2019)
The work environment is a very important factor within any institution since this is part of the context where employees work and is reflected in the development of their daily activities, because there are components such as lack of communication, demotivation, the tense environment, the conflict and others that negatively influence within a company or department such as the Financial Administrative Unit of the Coordination of the Ministry of Inclusion, Economic and Social (MIES) of the city of Babahoyo, components that do not allow employees of this department culminate or carry out its activities within the time and space required with the quality, efficiency and effectiveness that is expected in its usual work by the institution